FINANCIAL ANALYSIS OF AUGERHOLE TECHNIQUES OF RAISING EUCALYPTUS AND BHABBAR IN LOWER SHIWALIKS - Agnihotri, Y.; Grewal, S.S. (Journal of Soil and Water Conservation, 2022)
Growing of eucalyptus in Shiwalik foothills is very popular because of its fast growth, coppicing ability and versatility to grow under diverse soil and climatic conditions. Bhabar, on the other hand, is a predominant common grass of the area which has been succesisfully grown under Eucalyptus. Planting of Eucalyptus in augerholes filled with original soil (OS) FYM I rice husk with varying depth has been found to accelerate growth of plants. More gross returns due to the augerhole technique of raising the plantation may be obtained at an increased cost. The present study aims to perform financial analysis of the Bhabbar + Eucalyptus system raised in augerholes of various depths and intercompares with the system grown with traditional method. Raising Eucalyptus in augerholes of size 6 cm x 120 cm filled with OS + 1 kg rice husk + 1 kg. FYM has given rise to the highest B/C ratio of 2.59 followed by the augerholes of the same dimensions filled with FYM. The B/C ratio in the latter case worked out to 2.49 at 12% discount rate.